Measurement of key factors affecting employee extra-role behaviour in Ministry of Municipalities and Public Works in Iraq - Al zubaidi, Salam Oleiwi Radhi (2014)
This study is about the employee extra role behavior and trust within an organization. The researcher has examined many variables including the psychological support, trust in management, reward expectation, management value and other motivational aspects of the research. The researcher has also made use of quantitative research methods to gather the information required for the research study which is limited to the Ministry of Municipalities and Public Works (MMPW) in Iraq. The gathered information was tested using Statistical Package for the Social Sciences (SPSS) for various tests such as regression and reliability scale to check for the reliability and validity and the results were very significant when the hypothesis were tested which were laid down earlier in the research study by the researcher.